Ecological knowledge and sustainable planning in Nigeria: a reflection on the Yorubas of South-Western Nigeria - Oladayo Ramon Ibrahim (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії, 2017)
In pre-colonial times, African people survived by acquiring and preserving community knowledge of the environment and the relationships between human and non-human elements. The paper is based primarily on secondary data, and examines the relationships between African people, especially Yoruba people of southwestern Nigeria and the land and how understanding this relationship can help our quest for a more effective and sustainable regional planning. The study   investigates the indigenous Yoruba Ecological Thoughts and Beliefs and how these affected the ways people have interacted with the environment. The result shows that there is a lot that modern planning can gain from the culture-environmental relationships of the indigenous people.